Development of self-assembled bacterial cellulose-starch nanocomposites - Grande, C.G.; Torres, F.G.; Gómez, C.M.; Troncoso, O.P.; Canet-Ferrer, J.; Martinez-Pastor, J. (Elsevier, 2009)
A bioinspired bottom-up process was developed to produce self-assembled nanocomposites of cellulose synthesized by Acetobacter bacteria and native starch. This process takes advantage of the way some bacteria extrude cellulose nanofibres and of the transport process that occurs during the gelatinization of starch. Potato and corn starch were added into the culture medium and partially gelatinized in order to allow the cellulose nanofibrils to grow in the presence of a starch phase. The bacterial cellulose (BC)–starch gels were hot pressed into sheets that had a BC volume fraction higher than 90%. During this step starch was forced to further penetrate the BC network. The self-assembled BC–starch nanocomposites showed a coherent morphology that was assessed by Atomic Force Microscopy (AFM) and Environmental Scanning Electron Microscopy (ESEM). The nanocomposites structure was studied using X-ray diffraction and ATR-FTIR spectroscopy. The degree of crystallinity of the final nanocomposites was used to estimate the volume fraction of BC. The aim of this paper is to explore a new methodology that could be used to produce nanomaterials by introducing a different phase into a cellulose nanofibre network during its assembly.
Keywords: Self-assembled; Bottom-up; Bacterial cellulose; Starch; https://purl.org/pe-repo/ocde/ford#1.06.00